Implementation of the Merdeka Curriculum in Grade 4 Integrated Science and Social Studies Learning at SDN Wailiti, Nusa Tenggara Timur: Opportunities, Challenges, and Strategies for Student-Centered Education - Dian Ernaningsih; Selvi Nena; Yulimira Syafriati Y. M. Sani (The Indonesian Institute of Science and Technology Research, 2026)
The Merdeka Curriculum represents a transformative approach in Indonesian primary education, emphasizing flexible, student-centered learning and holistic development. This study investigates the implementation of the Merdeka Curriculum in Grade 4 Integrated Science and Social Studies at SDN Wailiti, Nusa Tenggara Timur. Using a qualitative descriptive approach, data were collected through classroom observations, interviews with teachers and the principal, and documentation of learning activities. Findings indicate that the curriculum enables teachers to adapt materials according to student needs, promotes active and meaningful learning, and integrates project-based activities aligned with the Pancasila Student Profile (P5). Challenges identified include teachers’ difficulty understanding learning outcomes, limited instructional resources, and students’ concentration and conceptual understanding. Strategies to overcome these obstacles involve professional development, collaborative module design, utilization of digital learning resources, and inquiry- and project-based learning methods. The study highlights the importance of ongoing teacher support, adaptive teaching strategies, and resource optimization to enhance curriculum implementation, ultimately contributing to student engagement, critical thinking, and holistic competence.